Presepsin as a predictor of positive blood culture in suspected neonatal sepsis. Issue 2 (22nd February 2018) - Miyosawa, Yukihide; Akazawa, Yohei; Kamiya, Motoko; Nakamura, Chizuko; Takeuchi, Yusuke; Kusakari, Mai; Nakamura, Tomohiko
Abstract: Background: Although the incidence of neonatal sepsis is decreasing, neonatal sepsis remains a severe life‐threatening disease. No current biochemical marker can provide perfect diagnostic accuracy for neonatal sepsis. The aim of this study was therefore to evaluate the accuracy of presepsin (P‐SEP) as a novel biomarker of bacterial infection for neonatal sepsis diagnosis. Methods: We prospectively studied newborns with sepsis (sepsis group; n = 13) during the first 30 days after birth and compared them with control preterm newborns (control group; n = 18). In addition, we evaluated term newborns with some clinical signs of early onset sepsis (non‐sepsis term group; n = 35). Results: P‐SEP in the sepsis group was significantly higher than in the control group ( P < 0.001) The area under the curve for P‐SEP was 0.868 (95%CI: 0.71–1.00). A P‐SEP cut‐off of 795 pg/mL was established, with 85% sensitivity and 89% specificity. The positive and negative predictive values were 85% and 89%, respectively. In the non‐sepsis term group, P‐SEP had better stability than white blood cells and C‐reactive protein for 3 days after birth. Conclusions: P‐SEP can better discriminate between infections and non‐infectious inflammatory conditions than the currently used biomarkers.